Lutein and zeaxanthin supplementation in preterm infants to prevent retinopathy of prematurity: a randomized controlled study. - Dani, Carlo; Lori, Ilaria; Favelli, Federica; Frosini, Saverio; Messner, Hubert; Wanker, Petra; De Marini, Sergio; Oretti, Chiara; Boldrini, Antonio; Massimiliano, Ciantelli; Bragetti, Patrizia; Germini, Cristiana (J Matern Fetal Neonatal Med, 2012)
OBJECTIVES: Lutein and its isomer zeaxanthin (L/Z) function in the eye as antioxidant agents and blue-light filters. Our aim was to evaluate whether their administration could help decrease the occurrence of retinopathy of prematurity (ROP) in preterm infants. METHODS: Infants with gestational age ≤32 weeks were randomly assigned to receive a daily dose of L/Z (0.14 + 0.006 mg) or placebo until discharge. RESULTS: ROP occurrence was similar in the L/Z (11/58; 19%) and placebo (15/56; 27%) groups, as the occurrence of ROP at each stage and the need of eye surgery. CONCLUSION: L/Z supplementation was ineffective in preventing ROP in preterm infants and did not affect the outcome at discharge of our patients.
Keywords: Antioxidants; Drug Administration Schedule; Drug Combinations; Female; Humans; Infant, Newborn; Infant, Premature; Logistic Models; Lutein; Male; Retinopathy of Prematurity; Risk Factors; Treatment Outcome; Xanthophylls; Zeaxanthins